Perlindungan Hukum Konsumen Terhadap Pemanfaatan Reaktor Hidrogen Energi Guna Menghemat BBM pada Bengkel Karya Gemilang - Hendra Gunawan (Pusat Riset dan Inovasi Nasional, 2026)
The development of automotive technology continuously seeks solutions to improve human mobility and address environmental concerns. This study focuses on the Hydrogen Reactor (HHO) technology as an alternative solution for fuel efficiency and emission reduction, specifically examining the legal protection of consumers utilizing this technology at Bengkel Karya Gemilang. The research aims to analyze the legal framework of consumer protection in the context of new energy-saving technologies and to identify the legal responsibilities of business actors (workshops) and the rights of consumers. Employing a normative legal research method with a case study approach, the study analyzes the implementation of Law No. 8 of 1999 concerning Consumer Protection (UUPK) in the utilization of HHO reactors. The findings indicate that while the HHO reactor technology offers a potential 5-15% increase in fuel efficiency and CO emission reduction, its implementation introduces new legal challenges, particularly regarding product safety, standardization, and the obligation for periodic servicing. Consumer protection is primarily ensured through the workshop’s obligation to provide clear product explanations, guarantee product safety, and fulfill the periodic service commitment. The study concludes that the existing UUPK provides a sufficient legal basis, but its implementation requires clear and transparent agreements, especially concerning the technical specifications and long-term maintenance of the HHO reactor, to ensure consumer rights are fully protected against potential risks associated with new, non-standardized automotive technologies.